2017
DOI: 10.1016/j.ijpe.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mergers and acquisitions on shareholders' wealth in the logistics service industry

Abstract: This is the other version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
(101 reference statements)
2
22
0
Order By: Relevance
“…Second, the long term stock returns performance is measured with the help of Buy-and-Hold Abnormal Returns (BHAR). In the financial researches, this approach is used (26) , Further, this technique is also used in M&As so that short term and long term impact of M&As can be analyzed and these synergies impact on the firm performance in terms of stock returns could be assessed (27) . The market model has been employed to estimate abnormal returns in the event window of 91 days.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the long term stock returns performance is measured with the help of Buy-and-Hold Abnormal Returns (BHAR). In the financial researches, this approach is used (26) , Further, this technique is also used in M&As so that short term and long term impact of M&As can be analyzed and these synergies impact on the firm performance in terms of stock returns could be assessed (27) . The market model has been employed to estimate abnormal returns in the event window of 91 days.…”
Section: Methodsmentioning
confidence: 99%
“…Assumption 4. Successful CBM&A can increase the revenue of MNCs through mechanisms such as cost savings, increased profits, upscaling, and abundant resources as has been demonstrated in different economic sectors [67][68][69].…”
Section: Assumptionmentioning
confidence: 99%
“…Kiesel et al [17] examined the features of goods transport and storage of Qinghai Railway, and optimized RLP structure in terms of good diversity, marketing strategy, and intermodal transport, based on the production situation of railway goods and the design principles of RLP. From the perspectives of logistics safety, greenness, and social benefits, Binder et al [18] identified the factors affecting RLP's operational benefits, constructed a reasonable evaluation index system (EIS), and provided the intelligent park management center with the top and bottom design techniques for operation management platform.…”
Section: Introductionmentioning
confidence: 99%